2005
DOI: 10.1103/physrevlett.94.117802
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Shish-Kebab Structure in a Sheared Polyethylene Melt

Abstract: Scanning electron micrographs of a solvent-extracted sheared polyethylene (PE) blend revealed, for the first time, an unexpected shish-kebab structure with multiple shish. The blend contained 2 wt % of crystallizing ultrahigh molecular weight polyethylene (UHMWPE) and 98 wt % of noncrystallizing PE matrix. The formation of multiple shish was attributed to the coil-stretch transition occurring in sections of UHMWPE chains. Synchrotron x-ray data provided clear evidence of the hypothesis that multiple shish orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
250
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(259 citation statements)
references
References 17 publications
8
250
1
Order By: Relevance
“…44 Subsequent studies of stress-induced crystallization of polyethylene elucidated this mechanism and revealed the detailed structure of these morphological units, which were called shish kebabs. [45][46][47][48][49][50][51][52] The detailed structure of polyethylene shish kebabs were revealed in recent studies, showing that the shish were sub-lm to $10 lm in length, $2-3 lm in diameter and contained $10-50 extended chain segments. 51,52 Also, a blend study revealed that mainly ultra-high molecular weight polyethylene chains ($5-6 Â 10 6 weight-average molecular weight) were involved in shish formation by a coil-stretch mechanism.…”
Section: Stress-induced Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Subsequent studies of stress-induced crystallization of polyethylene elucidated this mechanism and revealed the detailed structure of these morphological units, which were called shish kebabs. [45][46][47][48][49][50][51][52] The detailed structure of polyethylene shish kebabs were revealed in recent studies, showing that the shish were sub-lm to $10 lm in length, $2-3 lm in diameter and contained $10-50 extended chain segments. 51,52 Also, a blend study revealed that mainly ultra-high molecular weight polyethylene chains ($5-6 Â 10 6 weight-average molecular weight) were involved in shish formation by a coil-stretch mechanism.…”
Section: Stress-induced Crystallizationmentioning
confidence: 99%
“…51,52 Also, a blend study revealed that mainly ultra-high molecular weight polyethylene chains ($5-6 Â 10 6 weight-average molecular weight) were involved in shish formation by a coil-stretch mechanism. 51 Further, multiple shish were observed to connect adjacent lamellar kebabs 51 in contrast to the earlier view that only one shish connected adjacent kebabs. 53 The formation of the shish structures was attributed to heterogeneous primary nucleation.…”
Section: Stress-induced Crystallizationmentioning
confidence: 99%
“…The surface area of a kebab on which both parent and daughter morphology can grow is denoted by ψ 1,p . Reproduced with permission of the copyright owner [5] For such experiments, a shear cell is combined with in-situ X-ray diffraction (XRD) [4,[48][49][50][51][52][53], birefringence [18,23,43], or light scattering [46], or examined ex-situ with microscopy [4]. The critical flow conditions are usually expressed in terms of stress [4,44], mechanical work [35,45], or shear rate for a fixed strain [43].…”
Section: State Of the Artmentioning
confidence: 99%
“…Hence, bimodal blends of polymers composed of small fraction of long-chain molecules in a short-chain polymer matrix have been explored to simplify the task. [21][22][23] Even though industrial polymers and bimodal blends of controlled polydispersity demonstrate qualitatively similar results in the onset of oriented morphologies, it is not clear to what extent the longest molecular chains in polymer ensemble control the crystallization of polymer, and how the rest of the molecules influence the flow-induced crystallization. The aim of this study is to understand the interaction between different kinds of chains in a polydisperse system and illustrate how the interaction between these chains affects the conditions required for the flow-induced nucleation in polydisperse polymers.…”
mentioning
confidence: 97%